Futurity in Phenomenology : Promise and Method in Husserl, Levinas, and Derrida - DeRoo, Neal, 1981- (Book collections on Project MUSE., 2013)
From Husserl's account of protention to the recent turn to eschatology in 'theological' phenomenology, the future has always been a key aspect of phenomenological theories of time. This book offers a sustained reflection on the significance of futurity for the phenomenological method itself. In tracing the development of this theme, the author shows that only a proper understanding of the two-fold nature of the future can clarify the way in which phenomenology brings the subject and the world together.